2007
DOI: 10.1007/s00405-007-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

Invasive aspergillosis of the paranasal sinuses and the skull base

Abstract: Invasive aspergillosis (IA) originating from the paranasal sinuses can cause an intracranial growth mainly along the skull base and larger vessels. This study reports our experience in the diagnosis and treatment of a series of patients with IA. A retrospective chart review of four patients with chronic invasive intracranial aspergillosis was performed. Clinical signs, physical examinations, radiographs, histological samples, and outcome were demonstrated. The patients demonstrated different symptoms like exop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Reportedly, patients with HIES and a defective Th17 response are at risk for invasive fungal infections (19,23). An impaired mucosal host defense, as demonstrated by defective IL-22 or IL-17A production, may have led to increased fungal colonization of the nasal cavity and paranasal sinuses, impaired epithelial integrity, and invasion of the deeper tissues (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, patients with HIES and a defective Th17 response are at risk for invasive fungal infections (19,23). An impaired mucosal host defense, as demonstrated by defective IL-22 or IL-17A production, may have led to increased fungal colonization of the nasal cavity and paranasal sinuses, impaired epithelial integrity, and invasion of the deeper tissues (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The patients present with symptoms like proptosis, facial swelling, ophthalmoplegia, loss of vision, and hypoaesthesia of the ophthalmic and maxillary nerve. Computed tomography and MRI usually show extensive sino-orbital and skull base lesions [3]. Only small series of patients with this infection have been described; the radiographic diagnosis of cerebral and craniofacial aspergillosis has varied and has been relatively nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive cranio-orbital aspergillosis originating in the sphenoid sinus is rare and mostly occurs in immunocompromised patients with poor outcomes [2]. Invasive aspergillosis originating from the paranasal sinuses can cause an intra-cranial growth mainly along the skull base and larger vessels [3]. Orbital invasion readily occurs due to breach of thin bony partition of lamina papyracea leading to proptosis and gradual loss of vision.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the effect of IA on the central portion of the face in immunocompetent individuals 1,2,4,5,11 . Thus far, no study has reported its occurrence in relation to cocaine abuse.…”
Section: Case Reportmentioning
confidence: 99%
“…The main routes of entry are the respiratory tract, skin, cornea, and ear, and the infection may be localized or disseminated by contiguity or vascular invasion 2,3 . Patients with an impaired immune system or with disrupted anatomical and physiological barriers are at a high risk of developing the invasive form of the disease, characterized by fungal hyphae in tissues, which is associated with high mortality rates 4 .…”
Section: Introductionmentioning
confidence: 99%